Cannabis and Driving Ability - Sevigny, Eric L (2021)
The aim of this review is to discuss recent evidence on cannabis and driving ability. In particular, the review examines experimental research on the acute effects of tetrahydrocannabinol (THC) on driving-related neurobehavioral skills and driving performance based on simulator and road course studies. The evidence indicates that certain driving abilities are significantly, albeit modestly, impaired in individuals experiencing the acute effects of THC. Treatment effects are moderated by dose, delivery method, recency of use, and tolerance development, with inconclusive evidence concerning the moderating influence of cannabidiol (CBD). Emerging research priorities include linking neurobehavioral deficits to specific decrements in driving performance, estimating the real-world implications of experimental driving impairment research, understanding how tolerance differentially affects driving impairment in different subgroups, and developing more evidence on CBD’s potential role in mitigating THC-induced impairment